Pengaruh Sanitasi Lingkungan Tempat Tinggal Dan Karakteristik Sosial Ekonomi Rumah Tangga Terhadap Terjadinya Diare Pada Balita Di NTT (Analisis Lanjut Data Susenas 2012) - Suanta, Martin (Bumi Lestari, 2016)
Diarrhea is one of the main reasons of infant mortality in Indonesia. Diarrhea is also a negative impact of interaction between human beings and the environment. The aims of reasearch to know the influence of environment sanitation of house area and social economical characteristics of household toward diarrhea at infant in NTT. Design used secondary data from Susenas 2012 by using household sample for 4 triwulan as many as 10,702 household in all the regencies/city. Unit of analysis consists of both household having infants suffer diarrhea and infants did not suffer from diarhea, so that the amount of household that was researched were as many as the amount of infants in the household namely 5.783. The analysis method was descriptive analysis and inferensial, meanwhile the tool of statistics was by using the logistics regression. The result showed that the variable influences diarrhea at children under five years based on logistics regression was environment sanitation that was non-improved source (OR = 1.484; 95%CI = 1.180 – 1.867), source of water that was non-improved source (OR = 1.516; 95%CI = 1.097 – 2.095), type of tile from soil (OR = 1.439; 95%CI = 1.139 – 1.818), age of infant less than 24 month (OR = 1.294; 95%CI = 1.043 – 1.606), education of household is low (OR = 1.412; 95%CI = 1.010 – 1.973), and without breast feeding (OR = 1.898; 95%CI = 1.001 – 3.601). There was a significant relationship between source of water, condition of improved source sanitation, type of tool, age of children under five years, education of the head of household, and breast feeding with the diarrhea at children under five years (p = 0.000). The risk factor that was proved to influence diarrhea at children under five years was source of water that was non-improved source, condition of environment of house area that was not healthy, type of tile from soil, age of infant less than 2 year, education of the head of household was low, and there was no breast feeding given.
Keywords: environment; sanitation; children under five years; diarrhea